Queues applied to telecoms : courses and exercises - Ravaliminoarimalalason, Toky Basilide; Randimbindrainibe, Falimanana (Networks and telecommunications series., 2023)
From queues to telecoms. Queues are, of course, omnipresent in our world, at the bank, the supermarket, the shops, on the road... and yes, they also exist in the domain of telecoms. Queues Applied to Telecoms studies the theoretical aspect of these queues, from Poisson processes, Markov chains and queueing systems to queueing networks. The study of the use of their resources is addressed by the theory of teletraffic. This book also outlines the basic ideas in the theory of teletraffic, presenting the teletraffic of loss systems and waiting systems. However, some applications and explanations are more oriented towards the field of telecommunications, and this book contains lectures and more than sixty corrected exercises to cover these topics. On your marks....